Fetal premature excess vertebral linear calcification: a case series - Bronshtein, Moshe; Gover, Ayala; Beloosesky, Ron; Bachar, Gal; Khatib, Nizar (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
During embryogenesis, the vertebrae begin development during the 6th week of gestation via two lateral chondrification centers per segment. It was assumed that when disruptions occur in the process of somitogenesis during membranous vertebral body formation, chondrification and ossification will follow the anomalous membranous vertebral body scaffolding, resulting in an anomalous vertebral formation, such as a hemivertebra. Another hypothesis is that hemivertebra may result from anomalous distribution of intersegmental arteries of the vertebral column. There is no description in the medical literature of “excess linear calcifications” of part of the fetal vertebra, characterized by the presence of linear calcifications in the vertebrae of a developing fetus. In the first two trimesters of pregnancy, the fetal vertebrae usually show three calcified points in an axial section: the vertebral body and two transverse processes. Premature linear vertebral calcification was defined as an anterior or posterior echogenic connection between two of the points (Fig. 1). In this study, we describe seven cases of premature fetal linear vertebral calcification.
Keywords: calcification; spine; fetal anomaly